Al-Barzakh in the Light of the Holy Quran and the Prophet’s Sunna - Shadi Fawzi Mohammad Bushkar (My University, 2007)
Thanks to Allah and peace be upon his last prophet Muhammad, In this thesis, I demonstrated the conception of Barzakh life (in Islam, the life or the period being spent after one dies till the Resurrection Day) which starts from dying and giving up the ghost, I also discussed how the dying Muslim believer should think good of the God and how bad consequences it could be for those who don t do so. Moreover, I ve showed what dying one faces of agonies of death. Then I showed the journey of Soul towards Heaven and how the Soul of a believer is being honored and an unbeliever is being punished and insulted. I also demonstrated the conception of Soul, and whether the Soul is being punished or the body or both of them, I discussed also whether souls meet and visit each others in the Barzakh and where the final destination of souls is. I ve also defined the TWO ANGELS, and what reasons lead to grave punishment and what reasons may save a Muslim from this punishment. I ve discussed also the hearing of dead people to what is being said by those who are alive. And how prophet Muhammad heard those who were being punished, this which has to do with the relationship between the dead people and the alive, and I also mentioned the good deeds that might benefit a Muslim when he is alive and after he dies, and what deeds being done by alive people may benefit the dead people, and many other issues related. At the end I discussed how the Barzakh life is ended by blowing the Horn (the Resurrection Day) and then the important results.

الحمد لله وحده، والصلاة والسلام على من لا نبيّ بعده، وبعد: في هذا البحث بسط لمفهوم حياة البرزخ، والتي تبدأ من وقت الاحتضار قبل خروج الروح، إلى حين خروجها، وواجب العبد المحتضر في تلك اللحظات أن يحسن الظنّ بالله تعالى، والوعيد لمن يسيء الظن بالله تعالى، وفيه ما يلاقيه المحتضر من سكرات الموت وشدّته، ثم رحلة الروح نحو السماوات العلى، وتكريم روح المؤمن، وطرد روح الكافر وإهانتها. وتعرضت لمفهوم الروح، وماهيّتها، وهل يقع العذاب عليها أم على البدن؟، أم عليهما معا؟، وهل تتلاقى وتتزاور الأرواح في حياة البرزخ؟، وأين مستقر الأرواح؟. وتعرضتّ للقبر وضمته، وفتنته، والتعريف بالملكين، وسؤالهما، وما هي الأسباب المقتضية لعذاب القبر؟، وما هي الأسباب المنجية منه؟. وبسطتّ الحديث عن سماع الأموات كلام الأحياء، وسماع الرسول أصوات المعذبين، وهو من مواضيع علاقة الأموات بالأحياء، وذكر الأعمال الصالحة التي ينتفعون بها في حياتهم ومماتهم من سعيهم في دنياهم، أو ما يصل إليهم من سعي الأحياء لهم، وقضايا أخرى عديدة ذات صلة بالموضوع، وفي الخاتمة بيان نهاية حياة البرزخ بالنفخ في الصور، ثم أهمّ نتائج البحث.
حياة البرزخ في ضوء الكتاب والسّنة